Foundation biology students’ critical thinking ability: Self-efficacy versus actuality - Rayner, Gerry; Papakonstantinou, Theo (Journal of University Teaching and Learning Practice, 2018)
Critical thinking (CT) is a highly valued skill, based on feedback from a wide range of stakeholders, and thus academics have long sought to embed CT into undergraduate curricula. In this study, we investigated foundation biology students’ self-efficacy of their CT skills (including three CT sub-elements), and whether such self-efficacies changed over a year of study. We also assessed students’ actual CT ability, and whether there were differences in self-efficacy and actual ability between male and female students. While students’ self-efficacy of their overall CT ability increased over the course of the year, this value was significantly lower than each of the CT sub-element efficacies, at both commencement and completion of the study. Conversely, students’ actual CT skills did not change over the year, although females scored higher than males in the one of the two units of study. We conclude that (i) there is a disconnect between our students’ self-efficacy of, and actual, CT ability; and (ii) there is a gender-based difference in their self-efficacy and actual CT ability. We recommend interventions to enhance foundation biology students’ understanding of CT and through this, improve the concordance between their self-efficacy of their CT skills and their actual CT ability.